Improving Administrative Proceedings - Janowicz, Zbigniew (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2022)
The paper is an English translation of “Uwagi o doskonaleniu postępowania administracyjnego” by Zbigniew Janowicz published originally in Państwo i Prawo in 1978. The text is published as a part of a section of the Adam Mickiewicz University devoted to the achievements of the Professors of the Faculty of Law and Administration of the Adam Mickiewicz University, Poznań.